Novel Therapeutic Targets and Emerging Treatments for Fibrosis - Timothy D. Hewitson (Frontiers Research Topics, 2018)
For decades we have known that the overgrowth, hardening and scarring of tissues (so-called fibrosis) represents the final common pathway and best histological predictor of disease progression in most organs. Fibrosis is the culmination of both excess extracellular matrix deposition due to ongoing or severe injury, and a failure to regenerate. An inadequate wound repair process ultimately results in organ failure through a loss of function, and is therefore a major cause of morbidity and mortality in disease affecting both multiple and individual organs.Whilst the pathology of fibrosis and its significance are well understood, until recently we have known little about its molecular regulation. Current therapies are often indirect and non-specific, and only slow progression by a matter of months. The recent identification of novel therapeutic targets, and the development of new treatment strategies based on them, offers the exciting prospect of more efficacious therapies to treat this debilitating disorder.This Research Topic therefore compromises several up-to-date mini-reviews on currently known and emerging therapeutic targets for fibrosis including: the Transforming Growth Factor (TGF)-family; epigenetic factors; Angiotensin II type 2 (AT2) receptors; mineralocorticoid receptors; adenosine receptors; caveolins; and the sphingosine kinase/sphingosine 1-phosphate and notch signaling pathways. In each case, mechanistic insights into how each of these factors contribute to regulating fibrosis progression are described, along with how they can be targeted (by existing drugs, small molecules or other mimetics) to prevent and/or reverse fibrosis and its contribution to tissue dysfunction and failure. Two additional reviews will discuss various anti-fibrotic therapies that have demonstrated efficacy at the experimental level, but are not yet clinically approved; and the therapeutic potential vs limitations of stem cell-based therapies for reducing fibrosis while facilitating tissue repair. Finally, this Research Topic concludes with a clinical perspective of various anti-fibrotic therapies for cardiovascular disease (CVD), outlining limitations of currently used therapies, the pipeline of anti-fibrotics for CVD and why so many anti-fibrotic drugs have failed at the clinical level.